Field Soil Investigation Analysis Using Drilling Methods for Planning the Construction of IKN Access Roads - Erika Anggelina Manik; Jody Martin Ginting (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2024)
Geotechnical drilling is a method of soil investigation to determine soil parameters for construction. Even though many service providers and contractors carry out geotechnical drilling in Indonesia, some companies still do not comply with standard rules and guidelines. Geotechnical drilling for the IKN Access Road Construction Planning Project is carried out in accordance with applicable provisions and guidelines. The soil conditions at this location are generally very good so no special construction is required. Errors encountered in geotechnical drilling include cleaning the hole before SPT testing, uneven drill handle length, inappropriate UDS sampling, and SPT hammers that do not meet specifications, etc., inaccurate identification of soil type, number of hammer blows per minute. not according to specifications, as well as sample transportation and storage processes that do not comply with specifications.